2011
DOI: 10.1007/s13596-011-0018-2
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive effect of Silymarin on DOCA salt induced hypertension in unilateral nephrectomized rats

Abstract: The objective of the present investigation was to evaluate the therapeutic efficacy of Silymarin in DOCA salt induced hypertension in unilateral nephrectomized rats. Unilateral nephrectomy was performed in female Wistar rats (150-200 g). A week after unilateral nephrectomy, hypertension was induced by DOCA (25 mg/kg, once a week; s.c; for 4 weeks) dispersed in cottonseed oil. The effect of Silymarin (300 mg/kg and 500 mg/kg, p. o., for 4 weeks) was evaluated in DOCA salt induced hypertensive rats. Systolic blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…The study showed that in rats with simultaneous hypertension and diabetes, hypertension prevented the diabetes-induced decrease in HR. This finding is similar to that of a previous report on simultaneous DOCA-salt-induced hypertension and type 1 diabetes (Jadhav & Upasani 2011) and might be due to sympathetic hyperactivity (Souza et al 2008).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The study showed that in rats with simultaneous hypertension and diabetes, hypertension prevented the diabetes-induced decrease in HR. This finding is similar to that of a previous report on simultaneous DOCA-salt-induced hypertension and type 1 diabetes (Jadhav & Upasani 2011) and might be due to sympathetic hyperactivity (Souza et al 2008).…”
Section: Discussionsupporting
confidence: 92%
“…1995; Ohtomo et al. 2008) and rats with deoxycorticosteone acetate (DOCA)‐salt‐induced hypertension (Jadhav & Upasani 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Milk thistle used for alcoholic liver damage, alcoholic induced liver diseases [32]. Used against diabetes mellitus disease [33].…”
Section: Ethno Botanymentioning
confidence: 99%
“…Moreover, silibinin reduced blood pressure and the incidence of postocclusion arrhythmias in spontaneously hypertensive rats, and it was suggested that this compound may be beneficial when used in hypertensive patients who develop acute myocardial infarction [6]. Silymarin exhibited significant antihypertensive activity in a DOCA salt model of hypertension [7]. In anesthetized open chest cats, silibinin lowered the amplitude and duration of diastolic blood pressure and produced a marked depression of cardiac contractility [8], suggesting that silibinin affects the hemodynamic properties of the heart.…”
Section: Introductionmentioning
confidence: 99%